Brief Web-Based Intervention for Depression: Randomized Controlled Trial on Behavioral Activation - Jelinek, Lena; Arlt, Sönke; Moritz, Steffen; Schröder, Johanna; Westermann, Stefan; Cludius, Barbara (JMIR Publications, 2020)
BackgroundWeb-based interventions have been shown to be effective for the treatment of depression. However, interventions are often complex and include a variety of elements, making it difficult to identify the most effective component(s). ObjectiveThe aim of this pilot study was to shed light on mechanisms in the online treatment of depression by comparing a single-module, fully automated intervention for depression (internet-based behavioral activation [iBA]) to a nonoverlapping active control intervention and a nonactive control group. MethodsWe assessed 104 people with at least mild depressive symptoms (Patient Health Questionnaire-9, >4) via the internet at baseline (t0) and 2 weeks (t1) and 4 weeks (t2) later. After the t0 assessment, participants were randomly allocated to one of three groups: (1) iBA (n=37), (2) active control using a brief internet-based mindfulness intervention (iMBI, n=32), or (3) care as usual (CAU, n=35). The primary outcome was improvement in depressive symptoms, as measured using the Patient Health Questionnaire-9. Secondary parameters included changes in activity, dysfunctional attitudes, and quality of life ResultsWhile groups did not differ regarding the change in depression from t0 to t1 (ηp2=.007, P=.746) or t0 to t2 (ηp2=.008, P=.735), iBA was associated with a larger decrease in dysfunctional attitudes from t0 to t2 in comparison to CAU (ηp2=.053, P=.04) and a larger increase in activity from t0 to t1 than the pooled control groups (ηp2=.060, P=.02). A change in depression from t0 to t2 was mediated by a change in activity from t0 to t1. At t1, 22% (6/27) of the participants in the iBA group and 12% (3/25) of the participants in the iMBI group indicated that they did not use the intervention. ConclusionsAlthough we did not find support for the short-term efficacy of the single-module iBA regarding depression, long-term effects are still conceivable, potentially initiated by changes in secondary outcomes. Future studies should use a longer intervention and follow-up interval. Trial RegistrationDKRS (#DRKS00011562)